2016
DOI: 10.4103/0189-6725.181621
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment options for septic arthritis of the hip in children

Abstract: Septic arthritis is the result of bacterial infection of the hip joint and is often found in infants and toddlers. It is the most common septic joint condition during growth and may cause the most devastating complications without prompt and proper treatment. Early diagnosis and intervention are required to avoid irreversible complications. This review documents the systematic approach to diagnosis and management of septic arthritis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…With an arthrotomy there is a better overview of the joint and sufficient irrigation can be performed, but it can possibly lead to prolonged recovery, a higher risk of avascular necrosis, and associated problems such as stiffness of the joint. 15 However, in the included studies these differences were not found. In the earlier published studies it was not specified whether the surgeons only performed an aspiration or also did a lavage or washout through the needle.…”
Section: Discussionmentioning
confidence: 89%
“…With an arthrotomy there is a better overview of the joint and sufficient irrigation can be performed, but it can possibly lead to prolonged recovery, a higher risk of avascular necrosis, and associated problems such as stiffness of the joint. 15 However, in the included studies these differences were not found. In the earlier published studies it was not specified whether the surgeons only performed an aspiration or also did a lavage or washout through the needle.…”
Section: Discussionmentioning
confidence: 89%
“…El-Sayed et al [14] found a success rate similar to open arthrotomy and a significantly shorter hospitalization duration using hip arthroscopy drainage and irrigation to treat septic hip arthritis in children. However, the use of hip arthroscopy in children requires special training and an experienced orthopedic surgeon in the field, as it could prove technically challenging [21].…”
Section: Discussionmentioning
confidence: 99%
“…While open arthrotomy remains the gold standard for treatment of adult and pediatric septic arthritis, arthroscopic lavage is an acceptable alternative in the appropriate patient and adequately-trained surgeon [3,4,10,11] . In general, hip arthroscopy is technically challenging but its ease has improved with more fellowship-trained surgeons learning the procedure earlier in their careers as well as improvements in surgical instruments and techniques [8,12] . It is frequently utilized for noninfectious pathologies such as femoral acetabular impingement, ligamentum teres tears, chondral lesions and/or labral tears [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Before the emergence of MRI, children who met Kocher criteria underwent hip aspiration to assist in the diagnosis of septic hip prior to surgical intervention [4,12] . The current study does not refute the study by Gottschalk et al regarding the importance of MRI utilization in the work up of suspected septic hip arthritis [4] and notes that arthroscopy is not indicated when extracapsular pathologies are found on pre-operative MRI -we would suggest that they are in fact contra-indicated in this setting.…”
Section: Discussionmentioning
confidence: 99%